2013
DOI: 10.1093/jxb/ert241
|View full text |Cite
|
Sign up to set email alerts
|

A type III ACC synthase, ACS7, is involved in root gravitropism in Arabidopsis thaliana

Abstract: Ethylene is an important plant hormone that regulates developmental processes in plants. The ethylene biosynthesis pathway is a highly regulated process at both the transcriptional and post-translational level. The transcriptional regulation of these ethylene biosynthesis genes is well known. However, post-translational modifications of the key ethylene biosynthesis enzyme 1-aminocyclopropane-1-carboxylate (ACC) synthase (ACS) are little understood. In vitro kinase assays were conducted on the type III ACS, At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 106 publications
(135 reference statements)
0
51
0
Order By: Relevance
“…Pathway(s) that regulate ACS7 expression are unclear at present. Despite lacking a potential phosphorylation site in the C terminus, ACS7 was recently shown to be phosphorylated by a calcium-dependent protein kinase (CPK) activity at the N terminus, and phosphorylation could also lead to protein stabilization and ethylene production (Huang et al, 2013).…”
Section: The Potentiation Of Ethylene Induction By Sa Is Associated Wmentioning
confidence: 99%
“…Pathway(s) that regulate ACS7 expression are unclear at present. Despite lacking a potential phosphorylation site in the C terminus, ACS7 was recently shown to be phosphorylated by a calcium-dependent protein kinase (CPK) activity at the N terminus, and phosphorylation could also lead to protein stabilization and ethylene production (Huang et al, 2013).…”
Section: The Potentiation Of Ethylene Induction By Sa Is Associated Wmentioning
confidence: 99%
“…Some 14-3-3 proteins have been reported to regulate ET biosynthesis, and consequently ET levels, by interacting with ACS isoforms and controlling their stability (Chang et al, 2009;Huang et al, 2013;Yoon and Kieber, 2013). We decided to examine the possibility that RCI1A could also control ET content by interacting with ACS proteins.…”
Section: Rci1a Controls Et Levels In Arabidopsis By Interacting With mentioning
confidence: 99%
“…Active roles of 14-3-3 proteins in plant hormone signaling have been reported for gibberellic acid, ABA, and brassinosteroids (Gampala et al, 2007;Schoonheim et al, 2007;Nakata et al, 2009). Recently, 14-3-3 proteins were found to interact in vivo with a subset of proteins linked to ET biosynthesis, including several ACC SYNTHASE (ACS) isoforms, regulating their activity (Chang et al, 2009;Huang et al, 2013;Yoon and Kieber, 2013), which strongly suggests that they also play a role in the ET response. Regarding the implication of 14-3-3 proteins in mediating stress signaling, a number of studies have demonstrated that they have an important function in plant responses to biotic stresses (Gökirmak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium may therefore be assumed to be upstream of auxin in gravity signalling, but pharmacological studies suggest that the first peak of the calcium response in stems and the plateau of the second response are both auxin-transport dependent (Toyota et al 2008a). Calcium chelator-induced loss of root gravitropism was compromised in ACS7 (key ethylene biosynthesis enzyme) mutant, suggesting that ACS7 is involved in gravitropism downstream to calcium (Huang et al 2013). Inhibitors of mechanosensitive ion channels reduce the sedimentation of starch-rich chloroplasts in gravisensitive stem cells (Friedman et al 1998).…”
Section: Calciummentioning
confidence: 99%